The Brantas River Crisis: the Sand Mining Problem and the Search for Solution - Nawiyanto, Nawiyanto; Krisnadi, IG; Endrayadi, Eko Crys; Handayani, Sri Ana; Salindri, Dewi; Calvaryni, Nina Mutiara (Paramita: Historical Studies Journal, 2020)
This article examines the dynamics of power relations in the Brantas River sand mining and its influences on the fate of the most important river of East Java. By relying on archival sources, contemporary newspapers, and oral history interviews, it is argued that the Brantas river crisis occurred due to the acceleration of sand extractions facilitated by improved extraction technology in the form of mechanical sand extracting machines and the growing demand for sand for infrastructure development. Automated sand mining caused damage to infrastructure and settlements in various places along the river from downstream areas that continue to creep upstream, as well as the loss of biodiversity richness. The search for a solution has been going on for some time but failed to stop mining and bring the Brantas River out of the crisis. The failure occurred not because of the absence of a legal protection, but the difficulty of implementing regulations in the field due to the involvement of unscrupulous officials and politicians in the Brantas sand business, as well as the temptation of large and comfortable profits from mining that lured sand miners amid the limited available alternative sources of livelihood.Ã‚Â Artikel ini membahas dinamika relasi kuasa dalam penambangan pasir Sungai Brantas dan pengaruhnya terhadap nasib sungai terpenting di Jawa Timur in. Dengan mengandalkan sumber arsip, surat kabar kontemporer, dan wawancara sejarah lisan, diargumentasikan bahwa krisis sungai Brantas terjadi karena percepatan ekstraksi pasir yang difasilitasi oleh perubahan teknologi ekstraksi dalam bentuk mesin diesel penyedot pasir mekanis dan meningkatnya permintaan akan pasir untuk pengembangan infrastruktur. Penambangan pasir mekanis menyebabkan kerusakan infrastruktur dan permukiman di berbagai tempat di sepanjang sungai dari daerah hilir yang terus merambat ke hulu, serta hilangnya kekayaan keanekaragaman hayati. Pencarian solusi telah berlangsung selama beberapa waktu, tetapi gagal menghentikan penambangan dan membawa Sungai Brantas keluar dari krisis. Kegagalan itu terjadi bukan karena tidak adanya payung hukum, tetapi kesulitan menerapkan peraturan di lapangan karena keterlibatan pejabat dan politisi yang tidak bermoral dalam bisnis pasir Brantas, serta godaan keuntungan besar dan mudah dari penambangan. memancing para penambang pasir di tengah sumber mata pencaharian alternatif yang tersedia terbatas.Ã‚Â